2007
DOI: 10.1243/14680874jer02406
|View full text |Cite
|
Sign up to set email alerts
|

Validation of engine combustion models against detailed in-cylinder optical diagnostics data for a heavy-duty compression-ignition engine

Abstract: Three different approaches for modelling in-cylinder compression-ignition engine processes for partially premixed combustion modes are compared with experimentally observed cylinder pressure and in-cylinder images of liquid-and vapour-fuel penetration, ignition, combustion, and soot formation in an optically accessible heavy-duty direct injection engine. A multi-dimensional computational fluid dynamics model for engine combustion, KIVA-3V, served as a common platform into which three different combustion submo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Furthermore, many soot models are phenomenologically based, so that the soot and soot luminosity predictions can be directly compared to the spatial and temporal evolution of in-cylinder soot observed in experiments. Indeed, in a previous study, the predictions of the same phenomenological soot model used in the current study agreed well with optical/imaging observations of the spatial and temporal development of in-cylinder soot [15]. Accordingly, with three-dimensionally resolved distributions of soot temperature and volume fraction, these models can predict the resulting soot radiative emission.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, many soot models are phenomenologically based, so that the soot and soot luminosity predictions can be directly compared to the spatial and temporal evolution of in-cylinder soot observed in experiments. Indeed, in a previous study, the predictions of the same phenomenological soot model used in the current study agreed well with optical/imaging observations of the spatial and temporal development of in-cylinder soot [15]. Accordingly, with three-dimensionally resolved distributions of soot temperature and volume fraction, these models can predict the resulting soot radiative emission.…”
Section: Introductionsupporting
confidence: 87%
“…The fuel was a 2007 emissions-certification grade ultralow-sulfur number 2 diesel fuel that was typical of U.S. diesel fuel, having a cetane number of 46. Additional fuel specifications can be found in [15].…”
Section: Fuel and Fuel Injectormentioning
confidence: 99%
“…A cartoon of one possible diesel low-temperature combustion process is provided in Fig. 5 [123,229,353,354].…”
Section: Low-temperature Combustion Compression-ignition (Diesel) Engmentioning
confidence: 99%
“…It was found that further refinement of the computational mesh would lead to the increase of computational time without significantly improving the accuracy of the prediction. The subgrid-scale turbulence-chemistry interaction is not taken into consideration for RCCI combustion due to its nearly complete premixed and/or partially premixed combustion as demonstrated by Singh et al [31]. In this study, the simulation started from IVC timing to EVO timing regardless of intake and exhaust processes.…”
Section: Test Engine and Model Validationmentioning
confidence: 99%